A Cross-Cultural Perspective of Supervisory Values: Reply - Peterson, Richard B. (Academy of Management Journal, 1972)
The article presents a reply to comments made by Daniel Robey on the author's article ?A Cross-Cultural Perspective of Supervisory Values,? in the March 1972 issue. Robey's comments claimed that because the author mailed surveys around the world, the study was actually cross-regional and not cross-cultural. The author agrees with Robey that in the technical sense, the study was cross-regional, but since the research focused on different countries, it was cross-cultural, as opposed to cross-institutional, which he claims was his original intent.